2011
DOI: 10.1002/dta.359
|View full text |Cite
|
Sign up to set email alerts
|

Detection of doping with rhGH: Excretion study with WADA‐approved kits

Abstract: The detection of recombinant human growth hormone (rhGH) doping using the World Anti-Doping Agency (WADA) approved kits is reported in this research. Twenty-five young male students were selected and divided randomly into two groups with six belonging to the placebo and nineteen to the administration group. Thirteen volunteers in one group were administered with a Chinese preparation of rhGH while six volunteers included in the other group were given rhGH made in Switzerland. Both preparations were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(27 reference statements)
0
10
0
2
Order By: Relevance
“…However, all female subjects were not pregnant. Although this finding cannot presently be explained, a similar observation for Kit‐1 was previously reported by Jing et al . Nevertheless, the results of confirmation analysis using Kit‐2 clearly were negative and no false positive findings were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all female subjects were not pregnant. Although this finding cannot presently be explained, a similar observation for Kit‐1 was previously reported by Jing et al . Nevertheless, the results of confirmation analysis using Kit‐2 clearly were negative and no false positive findings were found.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to investigate the effects of ethnicity in terms of reference‐population‐based judgments, and an ethnicity study of Caucasian and African athletes has been carried out . For practical application, excretion studies with a low dose of rhGH in Japanese males and with two rhGH preparations produced in China and Switzerland were attempted . Both the results clearly showed that the GH isoform differential immunoassay has high potential for detecting rhGH doping.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the assays had to be implemented worldwide in WADA-accredited laboratories [29], and several studies had to be conducted to establish decision limits allowing declaring a sample 'positive' or -to use the more correct term -declare a results an 'adverse analytical finding' . Studies from Japan [30] and China [31] have shown the efficacy as well as the inherent limitations in terms of the window of opportunity. The chance to catch the cheaters is highest within the first 24 h after injection, and rapidly drops thereafter.…”
Section: The Isoform Approachmentioning
confidence: 98%
“…In 2011, a controlled administration study with two preparations of recombinant hGH (Chinese and Swiss products, 0.1 IU/kg bodyweight) was conducted and the traceability of the drug (i.e. its influence on the circulating GH isoforms) was determined using the WADA‐approved analytical kits . Following a single injection, detection windows between 12 and 18 h were observed, while repeated hGH application (one injection/day over 14 days) allowed for hGH abuse detection up to 21 h after cessation.…”
Section: Peptide Hormones Growth Factors and Related Substancesmentioning
confidence: 99%